(untitled) (Research, Society and Development, 2023)
Amelogenesis imperfecta (AI) is a hereditary defect that occurs during tooth enamel development and can affect both the deciduous and permanent dentition. Despite the different types of classification, in all of them there are expressive consequences that affect the quality of life of the patients. The main objective of this study was to address the clinical, histological, imaging, and diagnostic aspects of AI described in the literature, highlighting the main treatment options and possible prognoses. A narrative literature review was carried out by means of a bibliographic search in books, gray literature, literature review articles, and clinical studies found in the Google Academic, PubMed, Scielo, and Lilacs databases, using the keywords: "Amelogenesis imperfecta", "Dental enamel", "Tooth abnormalities", and "Dental care". The inclusion criteria were research in Portuguese, English, and Spanish, and there was no time limit for the articles searched. We included papers that addressed general characteristics and main forms of treatment linked to the anomaly, and excluded in vitro, laboratory and animal studies. It was found that the treatment depends on the patient’s age, socioeconomic condition, type of AI, severity and clinical situation. The dentist can perform procedures such as the use of metal-ceramic crowns, glass ionomer cement, composite resin restorations or veneers to solve the situation in which the patient is. However, there is still no technique or material that is considered the ideal treatment for this condition, but a correct diagnosis will be fundamental for the choice of treatment.